(untitled) (Journal of the College of Basic Education, 2023)
Praise be to God, and in Him we seek help, and after...It is one of the attractive Arabic poetic arts, which is distinguished from other poetry arts.Innovative (such as Al-Mawalia, Al-Zajal, Al-Kan, Kan, and Al-Quma), (what has been termed(quartets) or (dubits). This was characterized by being sweetened by the rules of the Arabs and the scales ofmorphology, and the sweetness of rhythm, in addition to its association with the meanings of sentimental love full of emotions.Sincere and the motives of asceticism, mysticism and philosophical meditation.In my brief study, I tried to identify this new color, which is distinguished fromOur Arabic poetry is composed of fixed templates, represented by its sixteen axis. Although the nature ofOur flexible Arabic poetry - meter, rhythm, methods and meanings - worthy of pushing its masters toFlying in its vast expanse, exploring from its wellspring every new, desirable or funnyRequired - Structure and Significance.